Attitudes toward Christian church retailing: A study in Cape Town, South Africa. (28th November 2018) - Bundwini, Nqobile; Lappeman, James
Abstract: The temporal and eternal often cross paths in economic and financial transactions, with the blending of religion and commerce producing divergent views. Nevertheless, churches increasingly use commercial methods such as marketing and retailing for, inter alia, fundraising, connecting with congregations and keeping abreast of social, technological and economic changes. As with most businesses, churches may investigate their target consumers in order to align their efforts to meet the needs of consumers. The peculiar nature of religious consumption has both short‐term, product‐based needs and long‐term spiritual influences. This study investigated the attitudes of church members toward church retailing and various types of church retail products. A series of 26 in‐depth interviews were conducted for this study, resulting in antithetical attitudes toward the broad concept of church retailing, and with more distinct positive and negative attitudes toward particular product types. Generally, attitudes were more positive toward products perceived to be more authentic with regard to the religious mission of the church, and more negative toward products perceived as straying from it. Furthermore, attitudes in relation to church retailing were influenced by who the ultimate beneficiaries would be.